Pengaruh Cooperative Learning dengan Strategi Make a Match terhadap Pemahaman Kosa Kata Bahasa Arab Siswa di MTsN 17 Tanah Datar: Pengaruh Pembelajaran Kooperatif dengan Strategi Make a Match terhadap Pemahaman Kosakata Bahasa Arab Siswa - Zahra Syurfa; Nurlaila; Rizka Widayanti; Partomuan Harahap (Language Development Center, 2024)
Background: This study was motivated by the low understanding of students' Arabic vocabulary at MTsN 17 Tanah Datar. Purpose: This research aims to determine the effect of cooperative learning with the make a match strategy on students' vocabulary understanding at MTsN 17 Tanah Datar. Method: The research methodology uses a quantitative experimental approach with a quasi-experimental design. The population in this study were all students in class eighth at MTsN 17 Tanah Datar. Researchers used Total Sampling techniques in taking samples. The researcher chose class 8.A with a total of 21 students as the experimental group and class 8.B with a total of 20 students as the control group. The instrument for vocabulary learning results is in the form of test questions that have been validated by the validator. Results and Discussion: The Wilcoxon test results were obtained by Asymp. Sig. (2-tailed)=<0.001. This means Asymp. Sig. (2-tailed)=0.001 is smaller than 0.05 )0.001<0.05) and means that H1 is accepted. Conclusions and Implications: Based on the results of the test wilcoxon,the researcher concluded in this study that there is effectiveness of cooperative learning with the make a match strategy on vocabulary understanding at MTsN 17 Tanah Datar.